Mediação de conflitos nas escolas públicas da Diretoria de Ensino-Região de Assis-SP: estudo de caso da função de Professor Mediador Escolar e Comunitário. - Menezes, Eva Cristina Aurélio (2013)
In schools and various conflicts occur, in order to reduce them, the Department of Education of the State of Sao Paulo, through Resolution SE 19/2010, decided on the basis of Professor Mediator and Community School, which is part of School Protection Program, established by the Foundation for Development of Education. This study aims at investigating how Professor Mediator and Community School Board of Education-Region Assis-SP, is experiencing conflict situations in the school environment. The methodology used for the research was a qualitative approach with a case study. It was used for both semi structured interviews with four professors mediators belonging to the Board of Education and eight students from schools attended by these mediators. As tool for the analysis of the interviews we used the technique of the Collective Subject Speech. It was found that mediators receive support from the supervisory of the protection system of your school Teaching Board and not all receives the of school management. This will cause a feeling of devaluation and lack of motivation of their work. These educators believe that the schools are surrounded by many conflicts and that many of them have already come from the family relationship and complain of the lack of parental support. The most common types of conflicts that we found on a day-to-day are coping, sexuality touched on in the first grades of Basic Education and use of drugs in more advanced grades. To the students interviewed mentioned the conflict are the most common brawls. The results of the students testimonials evidence that the CEIP contributes to resolve conflicts in school because hears, orients, avoids aggressions and remakes friendships. Students report the importance of creating a culture of peace in schools and the CEIP and it helps a lot that the school improves his performance. The majority of students interviewees report that CEIP is more efficient to solve the problems in school, though other actors also agree that the school management also assist in this process. Finally, the professional has faced the most different situations in schools since students with pain, disregard for school rules, complaints by students against other students until situations in that need some advice. In this way, these professionals are constructing your identity for this new role. The research subsidizes the discussion about this function and contributes to the reflection of how the public policies are being implemented in practice.